General topology an introduction - Richmond, Tom (De Gruyter, 2020)
The first half of the book provides an introduction to general topology, with ample space given to exercises and carefully selected applications. The second half of the text extends this introduction to the field of asymmetric topology, which is a field of great interest for applications in computer sciences. Recurring themes include the interactions of topology with order theory and mathematics designed to model loss-of-resolution situations
Keywords: MATHEMATICS / Geometry / General; Topologie; Einführung